Desain Program Latihan Berbasis Prinsip Fitt (Frequency, Intensity, Time, Type) Guna Meningkatkan Kebugaran Fisik Personel Arff (Airport Rescue dan Fire Fighting) Bandar Udara Jenderal Ahmad Yani Semarang - Rizqillah, Zaki Abrian; Saputra, Surya Tri; Sundoro, Sundoro (Universitas Respati Indonesia, 2025)
This study aims to design a physical training program based on the FITT principle (Frequency, Intensity, Time, Type) to improve the physical fitness of ARFF (Airport Rescue and Fire Fighting) personnel at Jenderal Ahmad Yani International Airport in Semarang. The research employed a level 1 Research and Development (R&D) method, focusing on product design without field trials. Data were collected through observation, interviews, and document analysis during On the Job Training (OJT) at the research site. The findings revealed that ARFF personnel lacked a structured physical training program, as well as motivation and guidance for consistent exercise. The designed training program refers to the FITT principle and is tailored according to age groups and the personnel's fitness levels. It includes cardiovascular exercises, muscular strength training, and flexibility routines scheduled over five training days per week. The program was validated by a sports expert using an evaluation checklist and was deemed suitable for implementation in the ARFF work environment. The implementation of this program is expected to enhance the physical fitness of ARFF personnel and support their preparedness and performance in handling emergency situations at the airport.